Pengaruh Efektivitas Penerapan Anggaran Terhadap Penilaian Kinerja Pusat Laba Studi Kasus pada PT. Rahayu Santosa - Supardji, Supardji; Suherlin, Yulian (Jurnal Ilmiah Ranggagading (JIR), 2009)
The purpose of this research is to find out how far the influence of budget implementation effectiveness towards the performance evaluation of profit center. The research used descriptive qualitative analysis. The yield of the research shows that PT Rahayu Santoso has utilized budget in evaluating the performance of its resposibility center. It can be looked at the effectiveness of budget implementation where the budget becomes work orientation for every responsibility center, so delegation of authority and responsibility to all managers of responsibility centers have double duty and responsibility. Besides that the performance evaluation of the menagers of profit centers was done comparing determined budget with its realization by means of probability ratio : Gross Profit Margin, Operating Profit Margin, and Net Profit Margin. Keywords : Budget implementation; the evaluation of profit center